2022
DOI: 10.3390/genes13091651
|View full text |Cite
|
Sign up to set email alerts
|

Grp94 Inhibitor HCP1 Inhibits Human Dermal Fibroblast Senescence

Abstract: Researchers are paying more and more attention to aging, especially skin aging. Therefore, it is urgent to find an effective way to inhibit aging. Here, we report a small chemical molecule, HCP1, that inhibited the senescence of human dermal fibroblasts (HDFs). First, we performed morphological experiment and found that HCP1-treated HDFs were no longer elongated and flat compared to DMSO-treated groups. Next, we found that the number of β-gal positive cells decreased compared to DMSO-treated groups. Through fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Our experiment results of these research showed that during inhibiting SAHF formation, ANXA7 mainly worked in the nucleus, while Grp94 did not translocate into the nucleus, it worked in the cytoplasm. 36 The results of our laboratory showed that either high or low phosphorylation of the Ser93 site of HP1γ could inhibit the formation of SAHF in dermal fibroblasts, and the detailed molecular mechanism needs to be further studied. In addition, the different site phosphorylation of HP1γ might take place in different cellular locations.…”
Section: Discussionmentioning
confidence: 91%
“…Our experiment results of these research showed that during inhibiting SAHF formation, ANXA7 mainly worked in the nucleus, while Grp94 did not translocate into the nucleus, it worked in the cytoplasm. 36 The results of our laboratory showed that either high or low phosphorylation of the Ser93 site of HP1γ could inhibit the formation of SAHF in dermal fibroblasts, and the detailed molecular mechanism needs to be further studied. In addition, the different site phosphorylation of HP1γ might take place in different cellular locations.…”
Section: Discussionmentioning
confidence: 91%
“…Another key senescence-promoting marker that we identified was heat shock protein Hsp901b (aka Grp94), which was significantly elevated (319%, q = 0.003) in 25-mth-old mice. This Hsp901b has received much recent attention as a target to inhibit to prevent senescence in humans ( Cui et al, 2022 ) and positively correlates ( p < 0.05) with upregulated expression of IL-18 (an NLRP3 inflammasome cytokine) in our 25-mth-old colon cells. Finally, p21 ( Cdkn1a ) gene expression loss strongly positively correlated (R > 0.5, q < 0.05) with expression losses of multiple genes, including Ctnnb1 and Hmgb1 , as well as increased abundances in several Gn genera ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 97%
“…Radiation-induced senescence involves increased autophagy in lung cancer cells [ 18 ]. Senescent cells appear large, flattened, and irregularly shaped, which is attributed to increased mammalian target of rapamycin (mTOR) signaling [ 111 , 112 ]. Derivatives of indolo [2,3-a]pyrrolo [3,4-c]carbazole induce senescence by modulating AKT/mTOR/S6K signaling in breast cancer cells, lung cancer cells, and colon cancer cells [ 112 ].…”
Section: Role Of Autophagy In Senescencementioning
confidence: 99%